Attitude and intergroup anxiety generalisation as mediators of the secondary transfer effect of the contact-prejudice relationship among white South African Stellenbosch University students - Daiber, Cara (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.